In Vitro: Anthelmintic Activity of Aqueous Leaf Extract of Indigofera tintoria L Againts Haemonchus contortus - Setyono, Wahyu (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2024)
Gastrointestinal nematodes are one of the causes of reduced production efficiency in sheep and goats in Indonesia, especially the parasite abomasum Haemonchus contortus. This parasite causes the disease Haemonchosis which causes anemia and is fatal for productive sheep and goats. Economic losses caused by the morbidity and mortality of this parasite are quite high, so it can increase the cost of prevention and treatment of this disease. The aim of this study was to evaluate the inhibition of hatching eggs and mortality of adult H. contortus worms from Indigofera tintoria L leaf infusa on in vitro. Indigofera leaf infusa on was tested at five concentrations, namely 0% as negative control, 20%, 40%, 60% and 80%. Positive control used Albendazole with a concentration of 0,025 mg/ml. At the highest concentration of 80% indigofera leaf infusa on was able to inhibit egg hatching by 95,37% and had a mortality rate of 68,67% against adult H. contortus worms. The 80% concentration had the same effect when compared to the positive control using Albendazole. Phytochemical analysis of Indigofera tintoria L leaves containing condensed tannins.